Population growth, economic growth, and poverty reduction in Uganda: Theory and evidence - Stephan Klasen (Georg-August-Universität Göttingen, Volkswirtschaftliches Seminar, 2005)
This paper examines the link between population and per capita economic growth in Uganda. After showing that Uganda has one of the highest population growth rates in the world which, due to the inherent demographic momentum, will persist for some time to come, it then considers the impact of population growth on per capita economic growth. It finds that both theoretical considerations as well as strong empirical evidence suggest that the currently high population growth puts a considerable break on per capita growth prospects in Uganda. Moreover, it contributes significantly to low achievements in education, health, and poverty reduction and will make improvements in these areas very difficult. It may also be an important factor in the increase of inequality. If Uganda began a period of sustained fertility decline, the estimates reviewed here would suggest that this could boost medium term percapita growth rates by between 0.5-0.6 percentage points per year; considering the favourableage structure dynamics such a fertility decline would generate, per capita growth couldincrease by between 1.5 and 3 percentage points. It could also significantly contribute to improvements in poverty, inequality, education, and health outcomes. The note emphasizes the importance of a concerted effort to promote female education (including progression, completion, and secondary education), female formal sector employment, investments in reproductive and child health as well as family planning services, and government political leadership to promote smaller families.
Keywords: J1; I32; O15; 330; poverty; inequality; population growth; Mozambique